Introduction - Sakal, Halil Burak; Keskin, Tuğrul (Cappadocia Journal of Area Studies, 2022)
The last issue of our journal in 2021 includes five different articles. In this issue, we present three research articles, one on historical and two on current issues, an opinion piece, and a publication review. Valeriy Morkva, in his article on the history of the Caucasus and Russia, deals with the annexation of the Eastern Georgian kingdom Kartli-Kakheti by Russia at the beginning of the 19th century. Morkva argues that the control of Georgian territory enabled the Russians to pass the Caucasus mountains. Gaining a foothold in the Southern Caucasus like Kartli-Kakheti helped Russia gain supremacy over the North Caucasian highlanders and further its interests in the region between the Black and Caspian seas. In his article, Morkva analyzes the spread of Russian influence to the Southern Caucasus during the 18th century and evaluates the Russian policy towards Eastern Georgia in that period. One of the two research articles on current politics in this issue was written by Hasan Aydın. Aydın deals with the African policy of the United States of America. In this study, the African policy of the Trump administration is examined in comparison with the administrations of its predecessors, George W. Bush and H. Barack Obama. The final point reached in the study is that although some of the goals of the USA’s Africa strategy announced during the Donald Trump era were relatively achieved, the desired success could not be achieved in general. Another research article on current issues was written by Aygül Akkuş. Akkuş deals with climate change, one of today’s imminent and serious threats, from the perspective of ethics and justice. According to Akkuş, those most affected by the climate crisis are those least affected by it. This issue forms the basis of the concept of climate justice. In Akkuş’s study, climate justice and climate ethics policies and practices are examined in America, Asia and Africa continents comparatively. Considering that climate justice cannot be studied separately from climate ethics and that this is also an ethical issue, the study aims to address climate ethics and climate justice debates based on environmental ethics understandings. Samet İşbilen discusses the topics that have been hotly debated recently regarding the security of Asia-Pacific and Europe. In his review essay, İşbilen claims that the privilege of NATO under the US dominance in defense and security in the Euro-Atlantic region during the Cold War period prevented Europe from establishing an autonomous defense system. While considering the NATO-EU relations, İşbilen examines the position of the EU in the new world order shaped by AUKUS. The only book review we have included in this issue belongs to Antony Hoyte-West. Hoyte-West offers a comprehensive review of the book entitled "Rodina: Tussen lethargie en revolutie, Amsterdam" written by Arnout Brouwers and released in 2018.